Boccia as an adapted and sensitizing sport in Physical Education in Secondary Education - Abellán, J.; Sáez-Gallego, N. M.; Carrión Olivares, S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
Adapted sports are being included in physical education programming. The present work evaluates the effect in the attitudes toward disabilityin Physical Education of the realization of a didactic unit of boccia following the teaching games for understanding’ perspective and an inclusive tournament with people with intellectual impairments of a group of secondary school students. Additionally, student’s opinion about boccia has been collected as sports content in Physical Education. The results indicate that participants improved their attitudes toward disability in Physical Education. In addition, participants indicated that the boccia contributes to values ​​education and equal opportunities, but not to the development of basic skills and abilities. The students only perceive the boccia as a sensitizing sport, for which reason it is necessary to continue investigating in this line to improve their opinion as sports content in Physical Education.